Sherlock Holmes. Volume 1 : the complete novels and stories - Doyle, Arthur Conan, Sir, 1859-1930.; Bantam Dell. (New York : Bantam Dell, 2003)
Presents Sir Arthur Conan Doyle's early novel "A Study in Scarlet," which introduced the character of Sherlock Holmes; and includes the novel "The Sign of Four," as well as thirty-six short stories.
Young Adult.
Young Adult
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Holmes, Sherlock (Fictional character) -- Fiction; Mystery fiction; Short stories